(untitled) (Universal International Scientific Journal, 2026)
The article discusses the importance of alternative energy sources - solar, wind, hydropower, geothermal energy and biomass energy, their mechanisms of operation, and their environmental and economic advantages. It also analyzes state policy aimed at developing renewable energy sources in Uzbekistan.